Technical Factors that Influence the Production of the Two Boats Lift Net in the Waters of the Kao Bay, Halmahera - Kadir, Irwan Abdul; Taeran, Imran; Surahman, Surahman; Rumagia, Faisal (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
Lift net used for fishing is outfitted with a number of facilities that, in theory, are highly crucial to the production process. Technical units can refer to these auxiliary equipment such boats, waring, lights, and rollers. Fishermen tend to increase the technical unity of the lift net, according to subjective habits and opinions without ensuring effectively and efficiently. The study aimed to: 1) define the lift net fishery, which covers fishing units and how they operate; and 2) analyzing the technical factors of production that play a role in the lift net fisheries. The research was conducted in the village of Babaneigo in June 2022. A survey method including interview techniques and direct measurements was used to acquire the data. To conduct interviews, questionnaires were given out to respondents, who were fishers and owners of a certain chart. The information gathered includes information on the size of the boat, the size of the net, the number and intensity of lights, the number of trips made each month, the number of hauls made each night, the amount of gasoline used, and the duration of net immersion. Ship, net, and hauling time dimensions are among the data that require direct measurement verification. With a F count of 31.46 > 3.48, the result indicated that production technical parameters overall had a considerable impact on production. The two main variables that significantly impact the lift net production are the light capacity factor and the number of trips.